Theoretical calculation of the low-lying electronic states of the molecule BN. (January 2015) - Mahmoud, Salman; Bechelany, Mikhael; Miele, Philippe; Korek, Mahmoud
Abstract: The potential energy curves have been investigated for the 42 singlet, triplet, and quintet lowest electronic states in the Λ ( ± ) 2 s + 1 representation below 95, 000 cm −1 of the molecule BN via CASSCF and MRCI (singly and doubly excitation with Davidson correction) calculations. Eighteen electronic states have been investigated in the present work for the first time. The harmonic frequency ω e, the internuclear distance R e, the rotational constants B e, the electronic energy with respect to the ground state T e, and the static dipole moment have been calculated. A very good agreement has been noticed by comparing the present results with those reported in the literature, theoretically as well as experimentally. Highlights: Potential curves and dipole moment calculated for 42 singlet, triplet, and quintet states. The constants are T e, R e, ω e, and D e Eighteen electronic states were investigated for the first time.